ZAKAT AND RAMADAN PHILANTHROPY: AN EDUCATIONAL POLICY MODEL FOR SOCIAL EMPOWERMENT - Oktapiani, Marliza (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2025)
This study explores the role of zakat and Ramadan philanthropy in shaping an educational policy model aimed at fostering social empowerment. Utilizing a literature review methodology, this paper synthesizes existing research on the intersection of Islamic philanthropy, educational frameworks, and socio-economic development. The findings indicate that zakat and Ramadan-based charitable activities serve as essential mechanisms for addressing educational disparities and enhancing community resilience. A well-structured educational policy that integrates zakat allocation can promote financial sustainability in education and reduce social inequalities. Comparative analyses reveal that nations implementing structured zakat-based educational programs demonstrate improved literacy rates and economic mobility among marginalized populations. However, challenges persist, including regulatory limitations, inconsistent zakat distribution, and inadequate institutional governance. This study highlights the necessity of policy innovation to align Islamic philanthropy with contemporary educational demands. Furthermore, it underscores the need for a collaborative approach involving policymakers, religious institutions, and educational stakeholders to optimize the impact of zakat on social development. The implications of this research suggest that a zakat-driven educational model can serve as a viable framework for sustainable social transformation. Future studies should explore empirical assessments of zakat-funded education initiatives to strengthen evidence-based policymaking in this domain.